2018
DOI: 10.3389/fendo.2018.00688
|View full text |Cite
|
Sign up to set email alerts
|

Shared Decision-Making in Growth Hormone Therapy—Implications for Patient Care

Abstract: Several studies have shown that adherence to growth hormone therapy (GHT) is not optimal. There are several reasons why patients may not fully adhere to their treatment regimen and this may have implications on treatment success, patient outcomes and healthcare spending and resourcing. A change in healthcare practices, from a physician paternalistic to a more patient autonomous approach to healthcare, has encouraged a greater onus on a shared decision-making (SDM) process whereby patients are actively encourag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
23
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 90 publications
(118 reference statements)
1
23
1
Order By: Relevance
“…Nonadherence to rhGH treatment impacts growth response [27]. Consistently, and in concordance with the results of the ECOS study [8,24], patients with a higher adherence rate during 2 years showed higher HV (cm/year and SDS), and therefore greater height gain (SDS).…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…Nonadherence to rhGH treatment impacts growth response [27]. Consistently, and in concordance with the results of the ECOS study [8,24], patients with a higher adherence rate during 2 years showed higher HV (cm/year and SDS), and therefore greater height gain (SDS).…”
Section: Discussionsupporting
confidence: 81%
“…Our results also showed that the education level of the parents was associated with a greater adherence during the first and second year of rhGH treatment. Though this correlation has been previously reported (either with regards to the level of education of the mother, father or both) [30,31], the evidence has not been consistent [27].…”
Section: Discussioncontrasting
confidence: 71%
See 1 more Smart Citation
“…The ability to exclude non-adherence to treatment in non-responders by electronic monitoring therefore represents an important advantage in patient care. The recommended measures to promote adherence to treatment are directly related to the factors that contribute to poor adherence (3,9). But first, it is essential to have methods capable of objectively evaluating the degree of therapeutic adherence of patients with r-hGH deficiency.…”
Section: Discussionmentioning
confidence: 99%
“…For all long-term treatments, adherence is one of the factors that determines treatment success together with patient characteristics, therapy area challenges, treatment access, and healthcare provision (36). Individual responsiveness is therefore very likely influenced by adherence.…”
Section: Adherencementioning
confidence: 99%